Circular facts - Abu ElDahab, Mai; Choi, Binna; Pethick, Emily (Berlin : Sternberg Press, 2011)
Circular Facts is a collaborative endeavor between three European contemporary art organizations: Casco - Office for Art, Design and Theory, Utrecht; Objectif Exhibitions, Antwerp; and The Showroom, London, in partnership with Kunst Halle Sankt Gallen and Electric Palm Tree. The project acted as an informal think tank and a mutual support structure for the production and dissemination of artistic projects, and has culminated in an eponymous publication. The publication aims to gather a spectrum of perspectives to explore the roles of specific initiatives within their particular localities. The contributors have produced works that speak to their experiences within arts institutions, collaborative curatorial initiatives, and research networks, expanding on the relationship between institutions and artists, markets, local and international audiences, and current political climates.
boek